Effectiveness of ChKM solution compared to triple-antibiotic paste as an intracanal medicament for bacteria that cause a chronic periapical abscess - Malinda, Yuti; Azhara, Dea Hanin; Harnung, Kartikaning; Prisinda, Diani (Universitas Padjadjaran, 2022)
Introduction: Chronic periapical abscesses are caused by polymicrobial bacteria, including E. faecalis, S. mutans, S. sanguinis, and P. gingivalis. These bacteria can be eliminated with chlorophenol camphor menthol (ChKM) solution and triple-antibiotic paste (TAP) as an intracanal medicament. This study compared the effectiveness of ChKM solution to triple-antibiotic paste as an intracanal medicament for bacteria that cause a chronic periapical abscess. Methods: An experimental laboratory was conducted in-vitro with the microdilution method and optical density measurement using a spectrophotometer. The cell inhibition percentage was calculated to determine the MIC value. The MBC values were confirmed by cultivating the Mueller Hinton Agar samples, incubating them at 37°C for 24 hours, and observing bacterial growth. Bacteria did not grow in the medium at MBC value. The lower MIC and MBC were sensitive and could be an effective medicament choice. Results: The MIC ChKM solution inhibits E. faecalis ATCC 29212, S. mutans ATCC 25175, S. sanguinis ATCC 10556, and P. gingivalis ATCC 33277 were 4000, 4000, 2000, and 2000 µg/mL consecutively. While MIC of TAP were 6, 0.375, 0.75, and 1.5 µg/mL, respectively. Moreover, MBC of the ChKM solution were 32000, 32000, 8000, 8000 µg/mL and MBC of the TAP were 768, 24, 24, 96 µg/mL. Conclusions: ChKM solution and TAP effectively inhibited and killed E. faecalis, S. mutans, S. sanguinis, and P. gingivalis as an intracanal medicament, as seen from the MIC and MBC values. However, TAP is more effective than the ChKM solution because MIC and MBC values of TAP are much lower than the ChKM solution. This finding indicated that TAP is more effective at the lowest concentration than ChKM solution. It should be highlighted that this was an in-vitro study involving specific microbes; thus, further clinical research is needed.